Insomnia symptoms, fatigue, and future job exit in American older adults. Issue 2 (5th November 2020) - Sagherian, Knar; Byon, Ha D.; Zhu, Shijun; Rose, Karen
Abstract: Background: As older adults prolong working life and face age‐related health changes, insomnia symptoms and fatigue may jeopardize their ability to stay in the labor force. Our study explored the relationships between insomnia symptoms, fatigue, and job exit in workers aged 65 years and older. Methods: Data from the National Health and Aging Trends Study were used (2011–2017). The sample included 953 Medicare beneficiaries with paid work at the time of the interview. Workers were followed annually for 6 years to the time of job exit. Insomnia measures included the number and type of symptoms, and fatigue (measured as low energy). Crude and adjusted odds ratios and 95% confidence intervals were estimated within discrete‐time survival analysis. Models were adjusted for health, lifestyle, and sociodemographic characteristics. Results: At baseline, approximately 49% of workers had either one or two insomnia symptoms. Difficulty falling asleep and difficulty maintaining asleep were prevalent in 35% and 37% of the sample. Fatigue was common in <30% of the sample. Workers with difficulty falling asleep were 1.29 times at higher odds to have job exit when compared with workers with no insomnia ( p = 0.033). Conversely, fatigued workers were 0.73–0.77 times at lower odds to have job exit when compared with nonfatigued workers ( p < 0.05). Conclusion: Difficulty falling asleep negatively affects future work status, unlike feeling fatigued. Healthcare providers are encouraged to assess for insomnia and discuss treatments with workers, and workplaces should be flexible with the start of workdays to support worker longevity.